Blood Pump Surface Roughness: Hemocompatibility and Machining Optimization - Li, Hongyu; Wang, Yiwen; Wu, Xuefeng; Zhou, Lijie; Liu, Lijia; Fang, Yuan (ASAIO journal (1992), 2025)
Blood compatibility, defined as a material's ability to maintain blood flow without inducing coagulation or hemolysis, was investigated through surface roughness optimization in blood pump flow channels. This study examines how machining parameters (depth of cut, cutting speed, feed per tooth, and cutting width) affect surface roughness using orthogonal experiments, revealing their descending order of influence. Blood compatibility tests comparing cellular damage and adhesion across varying surface roughness levels demonstrated that rougher titanium alloy surfaces significantly increased hemolysis rates and promoted platelet adhesion, accelerating thrombus formation. Genetic algorithm optimization identified optimal parameters: 80 m/min cutting speed, 0.2 mm depth of cut, 1.25 mm cutting width, and 0.02 mm/tooth feed. These parameters minimize surface roughness while maintaining machining efficiency, crucially enhancing blood pump performance by reducing thrombogenic risks. The established evaluation system and parameter optimization methodology provide practical guidance for manufacturing blood-contacting medical devices with improved hemocompatibility.